2008
DOI: 10.1590/s1806-37132008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Desfecho do tratamento e confirmação laboratorial do diagnóstico de tuberculose em pacientes com HIV/AIDS no Recife, Pernambuco, Brasil

Abstract: OBJETIVO: Comparar a freqüência de desfecho desfavorável (óbito, abandono e falência de tratamento) entre pacientes com co-infecção tuberculose (TB)/HIV submetidos a tratamento para TB com confirmação etiológica do diagnóstico e pacientes co-infectados com TB/HIV e tratados sem confirmação diagnóstica. MÉTODOS: Coorte retrospectivo de pacientes co-infectados com TB/HIV que iniciaram tratamento para TB entre julho de 2002 e junho de 2004, em um serviço de referência para HIV/AIDS no Recife (PE) Brasil. A exposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 22 publications
(24 reference statements)
0
14
1
8
Order By: Relevance
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 69%
“…22 The TB cure rate achieved by this study were higher than the rates obtained by other national surveys with patients coinfected with HIV who achieved TB cure rates below 58.8%. [23][24][25] However, the success rates recorded for both groups of patients in the present study were lower than those observed in previous studies [26][27][28][29][30][31][32] of populations, containing varying percentages of HIV-infected patients, that had been treated under a directly observed therapy (DOT) Home-based care program for patients coinfected with tuberculosis and human immunodefi ciency virus program. Furthermore, the number of patients who attained a cure under either treatment program in the present survey did not reach the 85% standard set by the World Health Organization.…”
Section: Discussioncontrasting
confidence: 69%
“…They concluded that TB culturing is a potentially cost-effective tool for use among HIVpositive patients in resource-constrained settings, but integration with existing clinical systems and strengthening of post-analytical processes is required to maximize its impact. Maruza et al (2008) suggest that TB treatment of HIV/TB co-infected patients without etiologic confirmation at the discretion of experienced physicians in referral centres did not increase the risk of unfavorable outcomes. However some variables should be closely monitored due to increased risk, for instance: the presence of other opportunistic diseases, a low CD4 lymphocyte count, a high viral load, dyspnoea, disseminated TB and changes in the TB treatment regimen due to adverse reactions or intolerance.…”
mentioning
confidence: 88%
“…Estudos realizados para analisar a adesão dos pacientes com aids confirmam que se trata de um fenômeno complexo e multicausal e os fatores determinantes podem ser classificados em três categorias (MELCHIOR et al, 2007; -relacionados ao indivíduo e ao seu estilo de vida (receio de estigma e discriminação, uso de substâncias químicas, depressão, suporte social); -relacionados à doença e ao tratamento (tipo de regime medicamentoso, uso de outros medicamentos, efeitos adversos); multidisciplinaridade).…”
Section: Spire 2008)unclassified
“…Estudos no Brasil e no mundo abordam a temática da coinfecção (BRUNELLO, 2010;CHEADE et al, 2009;MARUZA;LACERDA, 2008;MIRANDA et al, 2009;MUNIZ et al, 2006), mas são escassos os que enfocam os aspectos psicossociais da coinfecção HIV/TB, restringindo-se principalmente a questões relacionadas com o tratamento.…”
Section: Introdução 20unclassified